The Strategy of the Nasdem Party in Confronting the Dominance of Major Parties in the 2024 Election in Tuban Regency - Asyrofuddin, Muhammad Isa; Usni; Murod, Ma’mun; Setiawan, Asep (International Journal of Science and Society, 2025)
This study analyzes the strategy of the Nasdem Party in responding to the dominance of major parties in the 2024 election in Tuban Regency. The research background highlights the complexity of local political competition, which is dominated by religion-based parties, as well as the crucial role of community leaders and local identity in shaping voter preferences. This study aims to identify the political strategies employed by the Nasdem Party and to reveal the challenges faced in enhancing electability and vote acquisition. A descriptive qualitative method is utilized, incorporating a data triangulation approach that includes in-depth interviews, document studies, and direct observations of political activities in the field. The findings indicate that the Nasdem Party adopts a strategy based on recruiting high-quality cadres, internal consolidation, and political marketing through the 4P approach (product, price, place, promotion), tailored to the socio-cultural characteristics of Tuban’s society. The primary challenges encountered include the dominance of major parties such as PKB and Golkar, shifts in voter preferences due to local and national issues, and competition among regional political figures. Although there has been an increase in electability at the regency DPRD level, the results have not yet met the targets for the provincial DPRD and national DPR-RI levels. In conclusion, the strategies implemented by the Nasdem Party have led to several positive achievements but still require further evaluation and refinement to address greater challenges in the future. This study provides practical contributions to the development of political strategies and offers recommendations for political parties in navigating elections, particularly in regions with complex political dynamics such as Tuban Regency.